Double-stranded RNAs that encode killer toxins in Saccharomyces cerevisiae: unstable size of M double-stranded RNA and inhibition of M2 replication by M1. - Sommer, S S (1984)
The sizes of M1 and M2 (but not L) change rapidly with growth, varying by perhaps as much as 33%. Size variation is seen within 76 generations. In addition, the exclusion of M2 by M1 or L-A-E [( EXL]) is mediated by inhibition of replication or segregation, not by enhanced degradation of preexisting molecules.